A significant systematic review: impact of school head leadership competencies on teacher development - Ambon, Josephine; Alias, Bity Salwana; Mansor, Azlin Norhaini (International Journal of Evaluation and Research in Education (IJERE), 2025)
This article critically examines the impact of school head leadership competencies on teacher continuous professional development (CPD). Utilizing the Preferred reporting items for systematic reviews and metaanalyses (PRISMA) guidelines, a comprehensive search analyze 1,041 English-language publications from 2020 to 2024 taken from the Scopus, Web of Science and Eric databases. These articles collectively underscore the transformative role of leadership in cultivating professional learning community (PLC) enhancing teacher outcomes and spearheading innovative approaches to CPD. The data were collected, reviewed, and underwent a peer-review process before a systematic review. This article synthesizes findings from final articles (n=29) into three main themes: leadership and PLCs, effects of PLCs on teacher outcomes, and innovative approaches to CPD. These themes facilitate not only the CPD of teachers but also contribute to the overall educational environment by fostering collaboration, innovation, and resilience to changes in educational standards and practices. The findings reveal that effective leadership competencies are instrumental in promoting a culture of CPD among teachers. The evidence suggests a compelling link between school head leadership competencies and significant advancements in teacher CPD. This review provides valuable insights for educational policymakers, school administrators and scholars, emphasizing the critical needs for targeted leadership training programs that enhance the efficacy of CPD initiatives.